Assessment of extragenital pathology frequency and structure in women with multiple pregnancy depending on the type of placentation - Siusiuka, V. H.; Babinchuk, O. V.; Shevchenko, A. О.; Kyryliuk, O. D.; Bohuslavska, N. Y.; Bachurina, O. I.; Ramenska, V. V.; Сюсюка, Володимир Григорович (My University, 2023)
Women with multiple pregnancies (MP) are a special contingent that requires absolute medical and psychological observation at all stages of everything. Careful monitoring of this contingent of pregnant women, prevention of the most frequent complications (premature birth, anemia, gestosis, fetal restriction), ultrasound monitoring of early periods allows using a differentiated approach to the management of cases and childbirth, contributing to reduction of perinatal morbidity and mortality.